Red dragon fruit (Hylocereus spp.) peel marmalade effectively improve blood glucose and lipid profile of hypercholesterolemic wistar rats - Putriningtyas, Natalia Desy; Permatasari, Intan; Oktaviani, Dita; Raha, Anastasia Servia; Wahyuningsih, Siti (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Polyphenols, antioxidants, dietary fiber, and vitamin contained in the red dragon fruit peel. Red dragon fruit peel can be processed into marmalade. Red dragon fruit peel marmalade has the potential to be a functional food. Functional food is food that has a physiological function based on scientific studies.Objectives: The objective of this study is to analyze the effect of red dragon fruit peel marmalade on fasting blood glucose levels, HDL, LDL, and triglycerides levels of hypercholesterolemic Wistar rats.Methods: This study used a pre-&post-test control group design. Hypercholesterolemic male Wistar rats were randomly assigned into five groups. Hypercholesterolemia was induced by 1% cholesterol powder and 0.5% cholic acid for two weeks. All groups received standard chow. Samples were grouped into five groups: K-; K+; K1 (0.94 g/kg b.wt/day); K2 (1.41 g/kg b.wt/day); K3 (1.88 g/kg b.wt/day). The intervention was carried out for 28 days. GDP level was measured using the GOD-PAP. HDL, LDL, and triglyceride were analyzed with spectrophotometry. GDP, HDL, LDL, and triglyceride levels were measured twice before fasting. A paired t-test and one-way ANOVA were used to analyze the data.Results: The result showed that K-; K1; K2; K3 had a significant difference between groups before and after the intervention (p<0.05). Red dragon fruit peel Marmalade was able to reduce the levels of GDP, LDL, triglycerides, and increase HDL (p <0.05).Conclusion: Red dragon fruit peel marmalade reduced fasting blood glucose levels, LDL, triglyceride levels, and increased HDL levels of hypercholesterolemic Wistar rats.